Evaluation of Genotoxic and Cytotoxic Activities of Eremomastax speciosa (Hochst.) Cufod. (Acanthaceae) Leaf Extract - Chinyelu Clementina Osigwe; Jude Efiom Okokon; Ugonma Florence Uwaeme; Ijeoma Lilian Ebere (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
There is a growing interest in the therapeutic potentials of natural products and the mounting need to ensure their safety and efficacy. Eremomastax speciosa (Hochst.) Cufod. (Acanthaceae) is one of such medicinal plants used traditionally to treat various diseases in Nigeria. The leaf extract was investigated for genotoxic and cytotoxic effects using Allium cepa test. The effect of the Eremomastax speciosa leaf extract on the root meristem cells of Allium cepa bulb was investigated using onion bulbs exposed to varying concentrations of the extract (2.5 mg/mL, 5 mg/mL, and 10 mg/mL) for macroscopic and microscopic analysis. Tap water was used as a negative control and Methotrexate (0.1 mg/ml) was used as a positive control. There was statistically significant (p< 0.05) inhibition of root growth depending on concentration by the extract when compared with the negative control group. All the tested concentrations of extract were observed to have cytotoxic effects on cell division in A. cepa. The extract-induced chromosomal aberrations and micronuclei (MNC) formations in A. cepa root tip cells were significant (p<0.05) when compared with control group. The extract treatment further induced cell death, ghost cells, cells membrane damage, and binucleated cells. These results suggest that the leaf extract of Eremomastax speciosa possess cytotoxic and genotoxic effects on A. cepa root meristem cells.